Bilateral pallidal stimulation for Wilson's disease. Issue 9 (3rd April 2013) - Sidiropoulos, Christos; Hutchison, William; Mestre, Tiago; Moro, Elena; Prescott, Ian A.; Mizrachi, Alejandro Valencia; Fallis, Melanie; Rughani, Anand I.; Kalia, Suneil K.; Lozano, Andres; Fox, Susan
ABSTRACT Background To report on the clinical efficacy of bilateral globus pallidus internus deep brain stimulation in a 29‐year‐old patient with severe generalized dystonia secondary to Wilson's disease. Methods The primary outcome measure was the Burke‐Fahn‐Marsden Dystonia Scale motor severity score (blinded assessment) and the secondary outcome measures were the Abnormal Involuntary Movement Scale (blinded assessment) and the Zaritt Caregiver Burden Interview score, at 20‐week postoperative follow up. Results There was a 14% improvement in the Burke‐Fahn‐Marsden Dystonia Scale motor severity score. Abnormal Involuntary Movement Scale score remained unchanged while the Zaritt Caregiver Burden Interview score improved by 44.4%. Conclusions Bilateral globus pallidus deep brain stimulation can be effective in ameliorating dystonia and caregiver burden in Wilson's disease. Outcomes may depend on the stage of the disease at which the surgical procedure is completed. © 2013 Movement Disorder Society